Optimization of stocking density for mono-sex Nile tilapia (Oreochromis niloticus) production in riverine cage culture in Bangladesh - Mrityunjoy Kunda (Elsevier, 2021)
Determining a suitable stocking density of fish for an ambient condition is very important for economic benefit in cage aquaculture, which is not yet tested for many species in Sylhet district of Bangladesh. Therefore, current research was conducted in order to explore the effect of various stocking densities on growth and production performances of mono-sex Nile tilapia cage aquaculture in an open running water body, the Gurukchi River. Considering maximizing economic benefit, it is the first instance of such research in the Sylhet district of Bangladesh. In the three treatments (T1, T2, and T3), fingerlings were stocked at 40, 60 and 80 fish/m3, respectively with initial weights of 39.51 ± 0.91, 39.61 ± 0.71 and 38.54 ± 0.57g, respectively. Fish were fed with commercial floating pellet feed at 8-4% of their body weight. The results showed that growth performance of Nile tilapia significantly decreased with increasing stocking density. The mean total yields were 13.25 ± 0.48, 18.43 ± 0.88 and 22.76 ± 0.63 kg/m3 in T1, T2 and T3, respectively, which showed significant variations (p < 0.05) among treatments. The benefit-cost ratio analysis revealed that T1 (1.512 ± 0.022) and T2 (1.499 ± 0.063) were significantly (p < 0.05) higher than T3 (1.191 ± 0.071), with no significant differences observed between T1 and T2. Notably, a significantly higher (p < 0.05) net profit was observed in T2 than in T1 and T3. Overall, 60 fish/m3 stocking density was the best stocking density for commercial cage aquaculture of tilapia in a riverine environment of the north-eastern Bangladesh.